THE IMPACT OF THE INTERNATIONAL MONETARY FUND ON NATIONAL ECONOMIES AND ITS ROLE IN GLOBAL CRISES - Boliev Shokhruz Alisher ugli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT The International Monetary Fund (IMF) is an international organization aimed at  ensuring  global  economic  stability  and  supporting  the  financial  sustainability  of countries. This article analyzes the impact of the IMF on the economies of various countries,  elaborating  on  its  main  functions,  lending  policy,  role  in  strengthening financial stability, contributions to economic reforms, and significance during periods of global crises. Additionally, the article discusses the advantages and disadvantages of  IMF  operations  and  presents  conclusions  regarding  its  influence  on  national economies.